Ant-inspired strategies for opportunistic load balancing in the distributed computation of solutions to embarrassingly parallel problems - Engelbrecht, Andries P. (University of Pretoria, 2018)
Dissertation (MSc(Computer Science))--University of Pretoria, 2016.